Adaptive evolution of Schizochytrium sp. by continuous high oxygen stimulations to enhance docosahexaenoic acid synthesis. (July 2016) - Sun, Xiao-Man; Ren, Lu-Jing; Ji, Xiao-Jun; Chen, Sheng-Lan; Guo, Dong-Sheng; Huang, He
Highlights: Adaptive laboratory evolution improves microalgae growth performance. High oxygen adaptation increased DHA yield and changed oxygen sensitivity. Adaptive evolution enhanced ICDH enzyme activities and reduced ACL enzyme activities. Endpoint strains can obtain higher DHA percentage in high oxygen supply. The squalene content of endpoint strains was reduced by 63.08%. Abstract: Adaptive laboratory evolution (ALE) is an effective method in changing the strain characteristics. Here, ALE with high oxygen as a selection pressure was applied to improve the production capacity of Schizochytrium sp. Results showed that cell dry weight (CDW) of endpoint strain was 32.4% higher than that of starting strain. But slight lipid accumulation impairment was observed. These major performance changes were accompanied with enhanced isocitrate dehydrogenase enzyme activity and reduced ATP:citrate lyase enzyme activity. And a serious decrease of 62.6% in SDHA 140rpm → 170rpm was observed in the endpoint strain. To further study the docosahexaenoic acid (DHA) production ability of evolved strain, fed-batch strategy was applied and 84.34 g/L of cell dry weight and 26.40 g/L of DHA yield were observed. In addition, endpoint strain produced greatly less squalene than starting strain. This work demonstrated that ALE may be a promising tool in modifying microalga strains.